Plant form : an illustrated guide to flowering plant morphology - Bell, Adrian D.; Bryan, Alan (New York Oxford University Press, 1991)
Flowering plant exhibit an immense range of morphological features, that is to say details of form and modification of structure. A growing plant reveals all sorts of phenomena, presenting the observer with innumerable curiosities of shoot and root. This book allows the aspiring botanist and amateur horticulturist alike to discover the fascination of plant morphology perhaps for the first time. It is often stated that plant studies have progressed so far and so fast in the realms of ultrastructure and biochemistry that "basic" information is ignored. The student learns what is happening within a cell but can be ignorant of the whole plant, and lacks the knowledge to understand and describe even its most obvious features visible to the naked eye. This book is intended to redress the balance by providing a temptingly attractive and workable compendium of flowering plant morphology in a hitherto unobtainable form.
Donacion Dra. Elsa L. Cabral
Keywords: Morfologia de la Planta